Schoolchildren’s Competitiveness and Hubristic Motivation: the Dimensions and Assesment Posibilities - Nadyon, Viktoriya (Psychological Counseling and Psychotherapy, 2021)
Synopsis: According to results of theoretical analysis it was found that two competitive strategies are distinguished in children: interpersonal competitiveness and goal competitiveness. Interpersonal competitiveness (other-referenced competition) is considered as the striving to have better achievements than others and to win in interpersonal situations (games and activity) and to eSynopsis: According to results of theoretical analysis it was found that two competitive strategies are distinguished in children: interpersonal competitiveness and goal competitiveness. Interpersonal cnjoy the interpersonal competition and refers to hubristic striving for superiority. Goal competitiveness (task-oriented competition) is considered as the striving for excellence, goal achievement, and do one’s best and refers to hubristic striving for excellence and perfection. A Schoolchildren Competition Questionnaire was adapted. It consists of 17 items and characterized bi high rates of reliability and validity and describes three dimensions: 1) Other-referenced competition; 2) Task-oriented competition and 3) Maintenance of dominance hierarchy. It was revealed competitive strategies are connected with hubristic motivation in primary schoolchildren. Other-referenced competition characterizes schoolchildren with “Expressed dominance of pursuit for superiority”. The lowest level of is determined in children with “Low Hubristic Motivation”. The highest level of task-oriented competition characterizes schoolchildren with “Expressed Dominance of the pursuit of Excellence”. The lowest level of other-referenced competition and task-oriented competition is determined in children with “Low Hubristic Motivation”. Maintenance of dominance hierarchy characterizes schoolchildren with “Balanced Hubristic Motives”. The lowest level of maintenance of dominance is determined in children with “Moderate Dominance of the pursuit of Superiority”.